THE IMPACT OF LINGUISTIC AND CULTURAL EVENT ON THE EXPRESSION OF PERSONALITY TRAITS: A STUDY OF THE BIG-5 INVENTORY IN NON-CHINESE LANGUAGE LEARNERS - Goh Ying Soon; Lee Chai Chuen; Nor Azrina Mohd Yusof (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This study investigates the effects of engaging in Chinese cultural activities on the manifestation of personality traits in non-Chinese language learners, utilizing the BIG-5 Inventory as a measurement tool. The research aims to determine how involvement in cultural events such as the Mandarin Explorace, traditional attire design, and culinary workshops influences the five key dimensions of personality: openness, conscientiousness, extraversion, agreeableness, and neuroticism. Through an analysis of personality trait expression after participation in these culturally immersive experiences, the study seeks to elucidate the impact of cultural exposure on personality dynamics. The results are anticipated to enhance our comprehension of how cultural experiences can shape personality development and to offer insights into the role of cultural events in fostering intercultural competence and the holistic growth of language learners. The methodology involves post-event surveys, as to capture the changes in personality trait expression. The findings suggest that participation in these events results with increased openness and agreeableness, while also reducing neuroticism, indicating a positive influence of cultural immersion on personality development.